2013
DOI: 10.2174/1872213x113079990016
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes as Potential Carrier System for Targeted Delivery of Polyene Antibiotics

Abstract: The development of new therapeutic modalities involves the use of drug carrier, such as liposomes, which can modify pharmacokinetic and bio-distribution of drug profile. Polyene antibiotics incorporation into liposomes improves its availability at the site, bio-distribution and therapeutic index mainly through the engulfment of liposomes by circulating monocytes/macrophages and transportation to the site of infection. Polyene antibiotics (AmB, SJA-95, HA-1-92) and other antibiotics (streptomycin, tobramycin, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Research is beginning to exploit the strategy of receptor and ligand interaction, and make use of mannosylated “pathogen-like” polyanhydride nanoparticles for delivery of antigens into macrophages and DCs, the latter being another critical immune cell in innate and adaptive immunity [22,23]. Liposomes are often used as a carrier system for antimicrobial agents and, in general, to improve their bio-distribution, reduce cell toxicity, and increase the therapeutic index at the infection site [24]. In this regard, the MR represents a potential target for efficient delivery of mannosyated liposomes.…”
Section: Targeting the Mr To Tumor-associated Macrophages (Tams) In Cmentioning
confidence: 99%
“…Research is beginning to exploit the strategy of receptor and ligand interaction, and make use of mannosylated “pathogen-like” polyanhydride nanoparticles for delivery of antigens into macrophages and DCs, the latter being another critical immune cell in innate and adaptive immunity [22,23]. Liposomes are often used as a carrier system for antimicrobial agents and, in general, to improve their bio-distribution, reduce cell toxicity, and increase the therapeutic index at the infection site [24]. In this regard, the MR represents a potential target for efficient delivery of mannosyated liposomes.…”
Section: Targeting the Mr To Tumor-associated Macrophages (Tams) In Cmentioning
confidence: 99%
“…The main reasons for this finding are the suitable particle size of the AG-P-SS-P nanomicelles, which allows greater accumulation of PTX in tumor tissues due to the enhanced permeability and retention (EPR) effect, and the increased uptake of the AG-P-SS-P nanomicelles, which enhances their cytotoxicity in drug-resistant lung cancer cells. Additionally, the lack of toxicity observed in the various treatment groups (Additional file 1 : Figure S4A) indicated that the use of PEGylated materials in the AG-P-SS-P/PTX nanomicelles improved the pharmacokinetic profile of PTX [ 39 , 40 ], which ultimately resulted in higher accumulation in tumors. In addition, we did not observe any differences in the anticancer effects or toxicity to normal tissue between AG-P-SS-P nanomicelles and saline, indicating that AG-P-SS-P have no effect on A549/ADR-induced tumor-bearing mice (Additional file 1 : Figure S4A–D).…”
Section: Resultsmentioning
confidence: 99%
“…Nanotechnology has a great influence on the development of new drug delivery systems or nanoplatforms. By using these nanoplatforms, different advantages can be obtained, such as selectively transforming the delivery mode of related drugs [ 5 ], changing the distribution in the body through different targeting strategies [ 6 , 7 ], improving bioavailability [ 8 ], enhancing the efficiency of treatment [ 9 ], improving stability [ 10 , 11 ], and increasing the absorption of certain drugs through different mucosal tissue [ 12 , 13 ]. By the transdermal delivery routes, the local effects of nanoformulations can be enhanced to reach deeper layers of the skin; thus, the systemic bioavailability can be improved [ 14 ].…”
Section: Introductionmentioning
confidence: 99%